2014
DOI: 10.1370/afm.1625
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Stratified Care for Low Back Pain in Family Practice (IMPaCT Back): A Prospective Population-Based Sequential Comparison

Abstract: PURPOSE We aimed to determine the effects of implementing risk-stratified care for low back pain in family practice on physician's clinical behavior, patient outcomes, and costs. METHODSThe IMPaCT Back Study (IMplementation to improve Patient Care through Targeted treatment) prospectively compared separate patient cohorts in a preintervention phase (6 months of usual care) and a postintervention phase (12 months of stratified care) in family practice, involving 64 family physicians and linked physical therapy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
315
2
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 245 publications
(324 citation statements)
references
References 30 publications
4
315
2
3
Order By: Relevance
“…Data analysis and assimilation were subject to recommended procedures to ensure consistency and credibility, but combining un-related data from participants with different musculoskeletal pain conditions inevitably means that a certain degree of flexibility was required to reconcile features of both studies. Thus, it is recognised that findings could be vulnerable to redefinition with implications for the validity of our results, but there is no support in the literature to suggest sub-grouping by pain site is helpful when continued work participation is the aim, while there is evidence that non-specific chronic pain can be classified based on psychosocial complexity [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…Data analysis and assimilation were subject to recommended procedures to ensure consistency and credibility, but combining un-related data from participants with different musculoskeletal pain conditions inevitably means that a certain degree of flexibility was required to reconcile features of both studies. Thus, it is recognised that findings could be vulnerable to redefinition with implications for the validity of our results, but there is no support in the literature to suggest sub-grouping by pain site is helpful when continued work participation is the aim, while there is evidence that non-specific chronic pain can be classified based on psychosocial complexity [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…Les études en rhumatologie sont actuellement peu nombreuses. Dans le cas des lombalgies, la stratification de la prise en charge en soin primaire selon le niveau de risque de handicap des patients s'est montrée efficace du point de vue de la santé des patients et des coûts de santé [11]. Des démarches éducatives plus légères ont également été testées dans l'arthrose [12].…”
Section: Stratégies éDucativesunclassified
“…[5][6][7] Emerging evidence demonstrates that stratifying patients into more homogenous groups and offering targeted treatment leads to better patient outcomes. [8][9][10] The STarT Back Trial has demonstrated efficacy with respect to prognostic risk stratification on an individual basis within the controlled environment of a randomized controlled trial (RCT). 8 The translation of this model of care to everyday clinical practice is the next phase in the implementation of this system of care.…”
mentioning
confidence: 99%